Pengembangan Media Pembelajaran Matematika Berbasis Pendekatan Saintifik untuk Meningkatkan Kemampuan Komunikasi Matematis SMP Kelas VII - Suradi, Rahmat Ridho; Asmar, Ali; Yerizon, Yerizon (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Learning results found in several schools are still low. This happens because students do not understand the real life math problems that surround students, so students are lack of creative thingking. This is because the learning methods used by teachers have not been implemented optimally. One of effort that can be made to overcome these problems is to use learning media based on interactive multimedia in the mathematic learning for 7th grade of junior high school student who valid, practical and effective. This type of research is the development by using Plomp research design. During the initial survey phase, doing necessity analysis, curriculum analysis and conceptual analysis focused on issues related to learning mathematics. In the development phase or prototyping, the design of mathematics media learning based on a scientific approach to improve students' mathematical communication skills, then self-evaluation, one to one evaluation and small group evaluation. The assessment phase carried out a practicality test and a limited effectiveness test. Practicality data were obtained from teacher practicality questionnaires, student practicality questionnaires. Effectiveness data obtained from student result learning after implementing learning with learning devices. The research results showed that the mathematics learning media with macromedia flash based on scientific was valid and practical. Valid because it has qualify the valid criteria in terms of content and construct. Practical because they are easy to use and understand, the allocated allocations are very efficient, attractive, and contribute to learning. Effective in terms of its potential impact on students' mathematical communication skills